Northern fur seal diorama - Field Museum of Natural History (1940)
The Northern Fur Seal diorama is a notable addition to the Hall of Marine Mammals. The scene depicted is on St. Paul's Island, one of the Pribilof Islands in the Bering Sea. Forty mounted seals are included, showing old bulls with their ""harems"" of females and many small pups. A herd of young seals is shown in the background. Among these are some of the three-year-old males called ""bachelors,"" the surplus of which supplies the market with sealskin furs. Various seabirds such as the auklets and puffins, which nest in the seal rookery, are also shown.